Insulin glulisine in the management of diabetes - Yamada, Satoru (Dove Medical Press, 2009)
Insulin glulisine is appealing in principle, but the advantages of this drug over the other rapid-acting insulin analogs are still relatively unknown. The frequency of hypoglycemia, convenience in the timing of administration, and improvements in terms of HbA(1c) seem similar among the rapid-acting insulin analogs, including insulin glulisine. Only properly randomized long-term clinical studies with insulin glulisine will reveal the true value of this novel insulin analog.